Comparison of the Effects of Freshly Cooked or Reheated Mashed Potato, Prepared with Different Solid Fat Spreads, on Postprandial Glycemia. (29th May 2020) - Robertson, Tracey; Fielding, Barbara; Brown, Jonathan; Robertson, Denise
Abstract: Objectives: Resistant starch (RS) is classed as a dietary fiber and does not contribute to the postprandial glucose excursion. Two types may be formed during food processing: RS3 when a starchy carbohydrate cools; RS5 when starch is heated in the presence of lipid. It is unknown whether RS5 can be produced under domestic cooking conditions or whether different fat types would affect the amount formed. Nor is it known whether sufficient RS3 remains after a chilled meal is reheated to have a significant impact on the postprandial glucose response. The aim of this study was to determine if different solid fat spreads (of varying fatty acid composition) incorporated into a mashed potato meal, served either freshly cooked or chilled and reheated, would produce different effects on the postprandial glucose and insulin responses. Methods: Ten healthy adults (age: 29 ± 5 y; BMI: 21.7 ± 2.6 kg/m 2 ) attended six study days in a randomized crossover design. On each day, they consumed mashed potatoes (203 g) prepared with one of three solid fat spreads (butter, sunflower oil, olive oil, each providing 20 g fat). Each meal was consumed freshly cooked or microwave-reheated (after two days refrigeration at 4°C). Capillary blood samples were taken for 180 min postprandially. Plasma glucose and insulin were measured by glucose-oxidase method and ELISA respectively. Results: Glucose incremental area under the curve (IAUC) was significantly lower for the reheated meal with butter, compared to the equivalent freshly cooked meal ( P  = 0.030). Insulinogenic Index (IGI), a surrogate measure of first phase insulin response, was significantly lower for the freshly cooked butter meal in comparison with the reheated equivalent ( P  = 0.031). There were no other differences between meals, either for fat type or preparation method. Conclusions: Differences in RS formation may explain these results; work is underway to measure both total RS and RS5.  Other possible explanations are differences in effects on glucose absorption, such as via delayed gastric emptying. Whilst a beneficial effect on postprandial glucose and IGI was observed for the reheated butter meal, in comparison to the freshly cooked, it should be remembered that butter contains saturated fat, which has detrimental effects on blood lipids and should only be consumed in moderation. Funding Sources: Biotechnology and Biological Sciences Research Council, UK.